Intensified chipping during nanoindentation and the effect of friction on the interfacial fracture for thin films used in N/MEMS. (1st December 2022) - Dash, R; Bhattacharyya, K; Kumar, R P; Bhattacharyya, A S
Abstract: Nanoindentation was performed on Ti-B-Si-C and SiCN films deposited on Si substrates at varying loads and depths of penetrations. The intensity of chipping got enhanced with an increasing load which was represented geometrically. The pop-in and pop-out events occurring in the load and unloading were explained as cracking and high-pressure phase transformation. The interfacial fracture stability and adhesion of the film-substrate system, crucial for N/MEMS devices were analyzed with respect to frictional coefficient with the help of Finite Element Modelling (FEM).